PENGARUH IDOL K-POP SEBAGAI BRAND AMBASSADOR DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT - Alisa Qotrunnada; Dira Ayudirahma, Khotijah, Lavia Prakasiwa, Riza Fahlapi (Jurnal Ekonomi dan Bisnis, 2024)
This research is motivated by the increasing interest of teenagers in K-pop music and culture. K-pop idol groups often visit Indonesia to hold concerts, especially this year, for example the boy group Treasure will hold a concert in June 2024, and the boy group NCT will also hold a concert in Jakarta in May 2024. The concert will be held. This research focuses on examining how K-POP influences the young generation in Indonesia. The purpose of this study is to ascertain how brand awareness and image affect consumers decision-making process while making purchases. The data collected in this research was obtained through the use of a Google Form-based questionnaire as the main instrument for collecting responses from respondents. The method used is a quantitative method with a sample size of 104 respondents. The results of this research show that the recorded coefficient of determination is 0.730, which means that around 73% of the variation in purchasing decisions can be explained by the factors examined in this research. This proves that brand ambassadors and brand awareness play an important role in influencing purchasing decisions.